Angiotensin-Receptor Blockade Improves Inflammation and Endothelial Dysfunction in Ankylosing Spondylitis: ARB-AS Study - Garg, Nidhi; Krishan, Pawan; Syngle, Ashit (International Journal of Angiology, 2021)
Cardiovascular (CV) disease is the leading cause of premature death in ankylosing spondylitis (AS). Atherosclerosis and AS share similar pathogenic mechanisms. The proven benefits of angiotensin-receptor blockers (ARBs) in atherosclerotic cardiovascular disease and their role in immune mediation provide strong rationale to investigate its impact with olmesartan on inflammation and endothelial dysfunction in AS. To investigate the effect of olmesartan on inflammation and endothelial dysfunction in AS. 40 AS patients were randomized to receive 24 weeks of treatment with olmesartan (10 mg/day, n = 20) and placebo (n = 20) as an adjunct to existing stable antirheumatic drugs. Markers of endothelial function included the following: flow-mediated dilation (FMD) assessed by AngioDefender, endothelial progenitor cells (EPCs) estimated by flow cytometry, nitrite (nitric oxide surrogate), intracellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) and inflammatory measures including Bath ankylosing spondylitis disease activity index (BASDAI), ankylosing spondylitis disease activity score (ASDAS) and bath ankylosing spondylitis functional index (BASFI); erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP); proinflammatory cytokines (interleukin-1 [IL-1], IL-6, tumor necrosis factor-α [TNF-α]) and marker of oxidative stress– thiobarbituric acid reactive substances (TBARS) estimated at baseline and after treatment. Health assessment questionnaire disability index (HAQDI), 36-item short form survey (SF-36), and systematic coronary risk evaluation (SCORE) were estimated using standard tools. FMD improved significantly in the olmesartan group (5.83 ± 0.31% to 7.68 ± 0.27%, p  ≤  0.05) as compared with placebo (5.89 ± 0.35% to 6.04 ± 0.32%, p = 0.33). EPC population, nitrite, VCAM-1, and TBARS levels improved significantly in olmesartan group as compared with placebo (p ≤ 0.05). Olmesartan significantly decreased ASDAS, BASDAI, BASFI, ESR, CRP, IL-6, TNF-α, and SCORE as compared with placebo. HAQDI and SF-36 (PH) scores improved significantly in olmesartan group as compared with placebo. Olmesartan reduces inflammatory disease activity, improves quality of life (QOL), and decreases CV risk demonstrating the immunomodulatory, vasculoprotective, and cardioprotective potential of this drug in AS.
Keywords: Ankylosing Spondylitis; Endothelial Dysfunction; inflammation; Olmesartan